1985
DOI: 10.1128/iai.49.3.494-497.1985
|View full text |Cite
|
Sign up to set email alerts
|

Bacteroides endodontalis and other black-pigmented Bacteroides species in odontogenic abscesses

Abstract: Twenty-eight odontogenic abscesses were examined for the presence of black-pigmented Bacteroides spp. Of the 28 samples, 26 were found to contain one or more species of black-pigmented Bacteroides. Abscesses were divided into three categories according to the tissue of origin: endodontal, periodontal, and pericoronal. Four abscesses which developed after extraction were also examined. It was found that Bacteroides endodontalis, a newly described species of asaccharolytic black-pigmented Bacteroides, was isolat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

7
159
1
5

Year Published

1987
1987
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 263 publications
(172 citation statements)
references
References 20 publications
7
159
1
5
Order By: Relevance
“…aeruginosa and possibly S. epidermidis, the demonstrated bacteria occur in the oral cavity on the oral mucosa, the gingiva, the dorsum of the tongue, or the tonsils (32,33). The bacteria have also been demonstrated in the root canals of teeth with necrotic pulps (1,22,34), in deep periodontal pockets (35)(36)(37), and in acute abscesses of periodontal (26,38,39) or endodontic origin (23)(24)(25)(26). This study demonstrated these organisms in asymptomatic periapical lesions, and since several of the organisms are considered endodontic pathogens, it seems reasonable to hypothesize that they indeed caused or at least significantly contributed to the lesions.…”
Section: Discussionsupporting
confidence: 57%
See 1 more Smart Citation
“…aeruginosa and possibly S. epidermidis, the demonstrated bacteria occur in the oral cavity on the oral mucosa, the gingiva, the dorsum of the tongue, or the tonsils (32,33). The bacteria have also been demonstrated in the root canals of teeth with necrotic pulps (1,22,34), in deep periodontal pockets (35)(36)(37), and in acute abscesses of periodontal (26,38,39) or endodontic origin (23)(24)(25)(26). This study demonstrated these organisms in asymptomatic periapical lesions, and since several of the organisms are considered endodontic pathogens, it seems reasonable to hypothesize that they indeed caused or at least significantly contributed to the lesions.…”
Section: Discussionsupporting
confidence: 57%
“…Invasive capacity has been demonstrated for black-pigmented Bacteroides species (15)(16)(17), Actinobacillus actinomycetemcomilans (18,19), Capnocytophaga (20) and a number of other bacteria (21). The fact that several of these organisms have been implicated in some form of periodontal disease may indicate that invasiveness is an important aspect ofthe virulence of periodontopathic bacteria . These microorganisms have been demonstrated in infected root canals (1,2,22) as well as in pus from abseesses of endodontic origin (23)(24)(25)(26). Therefore, it was the purpose ofthe present investigation to examine patients with asymptomatie periapical inflammatory lesions that were refractory to endo-dontic treatment for extraradicular endodontic infections.…”
mentioning
confidence: 99%
“…Data shown are from one out of two experiments and represent mean value of triplicate cultures; the s.d. was < 10% in all cases.tThe Pi-specific CD4+ T cell clones F5, F7,14 and the SEA-reactive T cell line OV1 were generated from PBMC. $Below detection level (01 U/ml).…”
mentioning
confidence: 99%
“…Because endodontic infections are polymicrobial, the detection and identification of all associated organisms have been difficult and produced a great deal of confusing data. No absolute correlation has been made between any specific microbial species or combination of species with clinical signs and symptoms (14,(16)(17)(18)(19)(37)(38)(39)(40)(41)(42)(43)(44)(45)(46)(47)(48)(49)(50)(51)(52)(53)(54)(55).…”
Section: Sensitivity and Specificitymentioning
confidence: 99%
“…In the 1970s, it was then determined that most bacteria in endodontic infections are strict anaerobes (9)(10)(11)(12). The diversity of the polymicrobial endodontic infections has been well established with from three to 12 species of microbes isolated from the majority of endodontic infections (13)(14)(15)(16)(17)(18)(19).…”
mentioning
confidence: 99%